Novel immunotherapies in multiple myeloma: chances and challenges - Rasche, Leo; Wäsch, Ralph; Munder, Markus; Goldschmidt, Hartmut; Raab, Marc-Steffen (Haematologica, 2021)
In this review article, we summarize the latest data on antibody-drug conjugates, bispecific T-cell-engaging antibodies, and chimeric antigen receptor T cells in the treatment of multiple myeloma. We discuss the pivotal questions to be addressed as these new immunotherapies become standard agents in the management of multiple myeloma. We also focus on the selection of patients for these therapies and speculate as to how best to individualize treatment approaches. We see these novel immunotherapies as representing a paradigm shift. However, despite the promising preliminary data, many open issues remain to be evaluated in future trials.
Gesehen am 04.02.2022